An Instrument to Assess Self-Perceived Competencies in End-of-Life Care for Health Care Professionals: The End-of-Life Care Questionnaire. (December 2021) - Montagnini, Marcos; Smith, Heather M.; Price, Deborah M.; Strodtman, Linda; Ghosh, Bidisha
Purpose: We describe the development and the psychometric properties of an instrument to assess self-perceived EOL care competencies for healthcare professionals: The End-of-Life Care Questionnaire (EOL-Q). Methods: The EOL-Q consists of 28 questions assessing knowledge, attitudes and behaviors with subscale items addressing seven domains of care: decision-making, communication, continuity of care, emotional support for patients/families, symptom management, spiritual support for patients/families, and support for clinicians. The EOL-Q was used to assess competencies of 1, 197 healthcare professionals from multiple work units at a large medical center. Cronbach's alpha coefficients were calculated for the survey and subscales. A factor analysis was also conducted. Results: Internal consistency reliability was for was high for the total scale (0.93) and for the subscales addressing knowledge, behaviors, decision-making, communication, emotional support and symptom management (0.84-0.92); and moderate (>0.68) for the attitudes and continuity of care subscales. The factor analysis demonstrated robust consolidation of the communication and continuity of care subscales (eigenvalue 9.47), decision-making subscale (eigenvalue 3.38), symptom management subscale (eigenvalue 1.51), and emotional and spiritual support subscales (eigenvalue 1.13). Conclusion: Analysis of the psychometric properties of the EOL-Q care across settings supports its reliability and validity as a measure of self-perceived EOL care competencies in the domains of communication and continuity of care, decision-making, symptom management, and emotional and spiritual support. The EOL-Q displays promise as a tool for use in a variety of educational, research, and program development initiatives in EOL care.